Ancient warfare - Sidebottom, Harry (Oxford ; New York : Oxford University Press, 2004)
"This book explores the ways in which ancient society thought about conflict. Many aspects of ancient warfare are examined from philosophy to the technical skills needed to fight"--Provided by publisher.
Includes bibliographical references (p. 129-150) and index.
Keywords: Military art and science -- History -- To 500.; Military history, Ancient; Civilization, Western